PERAN ARSIPARIS SEBAGAI AGEN DALAM UPAYA MENEGAKKAN GERAKAN NASIONAL SADAR TERTIB ARSIP DI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN - Triana, Suci Septi; Putra, Riyan Adi (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2023)
Archivists can play a role in realizing the National Movement for Aware and Orderly Archives initiated by ANRI. This study aims to understand the role of archivists in record management as an effort to enforce the National Movement of Awareness and Orderly Archive in The Institute of Witness and Victim Protection. The type of research used is a case study with a qualitative approach. Techniques in data collection include observation, interviews, literature studies, and documentation. Data analysis techniques are data reduction, data presentation, triangulation, and conclusions. The results of this study revealed that archivists play a role in all stages of record management, creation, usage, storage, and disposition, as well as acting as a trigger in initiating the declaration of the National Movement of Awareness and Orderly Archive. Efforts made by archivists in dealing with the problem of archivists are accommodating internship activities to assist the work in managing archives, improving the quality of self by following the archiving training, discussing with leaders related to the implementation of archiving policies, and creative thinking while continuing to carry out their work despite obstacles.